Reassessment of the fiscal multiplier in developing countries: Regime-switching model - Michal Hlaváček; Ilgar Ismayilov; Ayaz Zeynalov (Charles University in Prague, Institute of Economic Studies (IES), 2020)
The existing literature on fiscal policy has mainly employed linear models that found a small fiscal multiplier in developing economies. These findings challenge the importance and effectiveness of fiscal policy for these countries. However, linear models are not capable of distinguishing the size of the fiscal multiplier in different phases of economic cycles. Responding to some recent studies that confirm regime dependency of a fiscal multiplier, our model enriches the literature of regime-switching models using a nonlinear panel threshold vector autoregression (PTVAR) model to measure the size of the fiscal multiplier for developing countries. Our finding confirms asymmetry in the response of GDP with regard to the economic situation. The main result of our paper shows that the response of GDP to government expenditure shock during a recovery period for developing countries is double that for developed ones. Our results also confirm a significantly larger fiscal multiplier during recovery compared to economic downturn.
Keywords: E32; E62; G15; C54; 330; Fiscal multiplier; developing countries; regime-switching; the panel threshold vector autoregression model